Rancang Bangun Aplikasi Perencanaan Persediaan Bahan Baku Pada UMKM Fredshoes - Fitriyaningrum, Lulut; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
SMEs (Micro, Small and Medium Enterprises) Fredshoes is one of the manufacturing company engaged in the production of safety shoes of various sizes, where business, combined with various motifs design life style fashionable your brand modern and unic prioritizing market appetite and transform safety shoes. Business process that has been happening is part of the production will be doing the production if there is an order from the customer. During this time, the company was not able to complete orders every month an average of 20 pieces of safety shoes received as scheduled because the recording of raw material inventory done manually which resulted in the accumulation of customer orders and can lead to errors in the calculation of the raw materials required.Based on these problems, the authors use the stages in the System Development Life Cycle (SDLC) in designing the system. The material of the raw material inventory planning using Economic Order Quantity (EOQ) to assist in the planning process of the production of raw materials.Based on the results of testing applications on SMEs Fredshoes it was concluded that the application has been made to produce information regarding reports of customer orders, reports the plan needs raw materials, the report plan needs raw EOQ, reports best-selling products and reports raw materials are often used which can be used by the SMEs as a basis in determining the ordering of raw materials.Â Keyword: inventory, raw materials, economic order quantity, application